Cognitive Gain in Digital Foreign Language Learning - Klimova, Blanka; Pikhart, Marcel (Brain sciences, 2023)
This systematic review examines the potential of digital language learning in contributing to students' cognitive gains. The study reviews existing research on the relationship between digital language learning and cognitive benefits, with a focus on enhanced problem-solving skills, memory, and multitasking ability. The research questions explored in this study are (1) does digital language learning contribute to cognitive gains in foreign language education? and (2) what are the pedagogical implications for cognitive improvement in digital foreign language education? The study employs the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology to identify and analyze relevant research articles. The results of the review suggest that working with printed texts may be more effective for cognitive gains compared to electronic texts. Additionally, implementing more senses through digital language education appears to be beneficial for cognitive gains. Thus, several pedagogical implications emerge for promoting cognitive improvement in digital foreign language education. Firstly, it is crucial to implement techniques and strategies that best align with students' language needs in a digital learning environment, whether it involves pen-and-paper activities or a flipped classroom approach. Secondly, exposing students to a variety of techniques that engage multiple senses can have a positive impact on cognitive gains. Finally, providing students with feedback is essential to maintain their motivation and foster continued progress in their foreign language studies.